2017
DOI: 10.5539/ibr.v10n10p182
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health and Safety in Small Enterprises: A Field Study in the Western Region of Saudi Arabia

Abstract: This research aims at familiarizing the business environment in Small Enterprises (SEs) in the Western Region of Saudi Arabia with occupational accidents that occur due to the lack of interest and belief of the enterprise administration in this issue, a trained supervisor, and the non-compliance of workers with the rules and regulations of Occupational Health and Safety (OHS). It also demonstrates the role of Civil Defense in reducing the number of such accidents. The research makes some recommendations that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…ISSN 2377-3219 2018 The job descriptions from the other sectors had moderate quality, such as manufacturing (3.6±0.2), education/training (3.5±1.0), construction (3.5±0.9) and SRD (3.3±0.6). The low quality of job descriptions from these sectors is in line with the low OSH performance found in other studies related to manufacturing sector (Al-Ghamri, 2017;Noweir, et al, 2013) and construction sector (Mosly, 2015;Al Haadir and Panuwatwanich, 2011). Furthermore, Kadasah (2015) concluded that the service sector and educational institutions came far after manufacturing sector in OSH performance.…”
Section: Evaluation Of Job Description Components According To Industsupporting
confidence: 57%
See 2 more Smart Citations
“…ISSN 2377-3219 2018 The job descriptions from the other sectors had moderate quality, such as manufacturing (3.6±0.2), education/training (3.5±1.0), construction (3.5±0.9) and SRD (3.3±0.6). The low quality of job descriptions from these sectors is in line with the low OSH performance found in other studies related to manufacturing sector (Al-Ghamri, 2017;Noweir, et al, 2013) and construction sector (Mosly, 2015;Al Haadir and Panuwatwanich, 2011). Furthermore, Kadasah (2015) concluded that the service sector and educational institutions came far after manufacturing sector in OSH performance.…”
Section: Evaluation Of Job Description Components According To Industsupporting
confidence: 57%
“…The official bodies necessitate that companies adopt OSH policies and also to pay great attention to the importance of safety means (Al-Ghamri, 2017). The reasons behind such growing interest in OSH are many, of which the low level of safety performance found in many studies (Taylan et al, 2017;Alsubaie, 2017;Ahmed et al, 2017;Al-Qubaisi, 2016;Mosly, 2015;Alolah et al, 2014;Noweir et al, 2013;Al Haadir and Panuwatwanich, 2011;Hassanain and Al-Mudhei, 2006) is an important one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation